Hydroxypropyltrimethyl ammonium chloride chitosan-based hydrogel as the split H5N1 mucosal adjuvant: Structure-activity relationship. (15th August 2021) - Fan, Qingze; Miao, Chunyu; Huang, Yilan; Yue, Hua; Wu, Anguo; Wu, Jianming; Wu, Jie; Ma, Guanghui
Abstract: In this study, 2-hydroxypropyltrimethyl ammonium chloride chitosan (HTCC)-based hydrogel was devised as a mucosal adjuvant for H5N1 vaccine. Aimed to investigate the structure activity relationship between HTCC hydrogel and immune response, we prepared a series of HTCC hydrogel with defined quaternization degrees (DQs, 0%, 21%, 41%, 60%, 80%). Results suggested that with DQ increasing, the positive charge and gelation time of HTCC hydrogel increased but the viscosity decreased. We applied in vivo imaging system and found that the moderate DQ 41% prolonged antigen residence time in nasal cavity, resulting in the most potent systemic responses (IgG, IgG1, IgG2a, HI). While, the lowest DQ 0% produced the best mucosal IgA antibody responses, most likely due to the closer contact with mucosa. Furthermore, the influence of animal gender was also discussed. These data add to the growing understanding of the relationship between physicochemical features of chitosan-based hydrogel and how they influence the immune responses. Highlights: Quaternized chitosan-based (HTCC) hydrogel was prepared as nasal adjuvant of H5N1. Quaternization degree (DQ) of HTCC hydrogel affected its physiochemical properties. Relationship between physiochemical properties and adjuvant activities was studied. Moderate DQ 41% elicited optimal IgG but lowest DQ 0% induced best mucosal IgA. Immune responses differed between sexes of mice.